2019
DOI: 10.2478/joim-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Relations of University Values and Competences of University Teachers

Abstract: Objective: The paper deals with the theoretical and empirical examination of university values in relation to key competences of university teachers. The combination of values that universities should prioritize and the competences that university teachers should possess is seen in the paper as an important precondition for improving the quality and acceleration of modern university progress. The theoretical part analyzes, compares and synthesizes opinions on key terms examined in the paper, i.e. higher educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…To this end, the results of calculating the transition in each core competency to determine the standardssetting appraisal measurement model indicated that instructors' competency levels had been assessed in a real-world context. The results are in parallel with those of past researchers' (Blašková & Blaško, 2012;Islam et al, 2019;Le, 2021;Prasetio et al, 2017;Turturean, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To this end, the results of calculating the transition in each core competency to determine the standardssetting appraisal measurement model indicated that instructors' competency levels had been assessed in a real-world context. The results are in parallel with those of past researchers' (Blašková & Blaško, 2012;Islam et al, 2019;Le, 2021;Prasetio et al, 2017;Turturean, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…These should be the core competencies model or used to identify a standard (Aliasghar et al, 2017). Each higher education instructor should follow this core competencies model in terms of behaviors and performance with regard to his or her work (Blašková & Blaško, 2012). Selvi (2010) listed nine core competencies as they apply to a higher education instructor: field competencies, research competencies, curriculum competencies, lifelong learning competencies, socio-cultural competencies, emotional competencies, communication c o m p e t e n c i e s , i n f o r m a t i o n a n d communication technologies competencies, and environmental competencies.…”
Section: Introductionmentioning
confidence: 99%